2017
DOI: 10.1007/978-3-319-67056-0_33
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Text Processing to Help Readers with Autism

Abstract: Autistic Spectrum Disorder (ASD) is a neurodevelopmental disorder which has a lifelong impact on the lives of people diagnosed with the condition. In many cases, people with ASD are unable to derive the gist or meaning of written documents due to their inability to process complex sentences, understand non-literal text, and understand uncommon and technical terms. This paper presents FIRST, an innovative project which developed language technology (LT) to make documents more accessible to people with ASD. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…ATS for Readers with Autism. The FIRST project (2012)(2013)(2014)(2015) was an EC-funded project under the FP7 ICT call concerning smart and personalised inclusion (Orȃsan et al, 2018). It provided OpenBook, a software that can automatically identify a range of language phenomena (e.g.…”
Section: Ats Projects For Social Goodmentioning
confidence: 99%
See 1 more Smart Citation
“…ATS for Readers with Autism. The FIRST project (2012)(2013)(2014)(2015) was an EC-funded project under the FP7 ICT call concerning smart and personalised inclusion (Orȃsan et al, 2018). It provided OpenBook, a software that can automatically identify a range of language phenomena (e.g.…”
Section: Ats Projects For Social Goodmentioning
confidence: 99%
“…The tool supported three languages: English, Spanish, and Bulgarian. Acknowledging that ATS was creating a large number of errors for some texts, and that end users have low tolerance for ungrammatical and erroneous text, OpenBook was also offering powerful post-editing options so that carers can post-edit the texts before showing them to the end users (Orȃsan et al, 2018). The architecture was highly modular, with separate modules for each transformation, to allow for highest level of personalization possible.…”
Section: Ats Projects For Social Goodmentioning
confidence: 99%
“…In terms of systems aimed at making text more accessible for autistic individuals who are fairly able, the OpenBook tool 1 is the most comprehensive existing system to date. The tool provides semi-automatic conversion of text documents by reducing syntactic complexity and disambiguating meaning by resolving pronominal reference, performing word sense disambiguation and detecting conventional metaphors Orȃsan et al, 2018), with some initial efforts towards concept substitutions for images (Barbu et al, 2015). As part of the research project, the tool was evaluated together with end-users with ASD who were shown to find the adapted texts more accessible than the originals.…”
Section: Automatic Text Adaptation For Adults With Autismmentioning
confidence: 99%
“…In many cases, text simplification is performed to facilitate subsequent human or machine text processing. This may include processing for human reading comprehension (Canning, 2002;Scarton et al, 2017;Orȃsan et al, 2018) or for NLP tasks such as dependency parsing (Jelínek, 2014), information extraction (Jonnalagadda et al, 2009;Evans, 2011;Peng et al, 2012), semantic role labelling (Vickrey and Koller, 2008), and multidocument summarisation (Blake et al, 2007;Siddharthan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…eye tracking (Klerke et al, 2015;Timm, 2018), and reading comprehension testing (Orȃsan et al, 2018) to evaluate text simplification systems.…”
Section: Introductionmentioning
confidence: 99%